A Hybrid Model of a Merit-Based Compensation System Based on Organizational Structure in the Banking Sector - Shokohsaljughi, Mahsa; Salajeghe, Sanjar; Anjomshoaa , Zahra (International Journal of Innovation Management and Organizational Behavior (IJIMOB), 2025)
Objective:  The aim of the present study was to examine a merit-based compensation system based on organizational structure within the banking sector.Methodology: This research was conducted using a mixed-methods approach. Participants in the qualitative section included academic experts and banking industry specialists, selected through purposive sampling. After 24 semi-structured interviews, theoretical saturation was achieved. In the quantitative section, all employees working at branches of Bank Keshavarzi participated. Sample size calculations were conducted using the G*Power software, and after accounting for response error, 386 responses were collected. Data analysis in the qualitative section employed open, axial, and selective coding methods within MAXQDA 2020 software. For the quantitative data, SPSS 26 and Smart PLS 3 software were used, and structural equation modeling was applied.Findings: The qualitative findings, using a paradigmatic approach, indicated that 26 categories were classified into six groupings: causal conditions, central phenomenon, intervening conditions, contextual conditions, solutions, and outcomes. On the other hand, the analysis of the conceptual model in the quantitative section revealed a significant positive relationship between all main factors.Conclusion: It can be concluded that focusing on each of the central and selective categories in the design of a merit-based compensation system based on organizational structure could result in positive outcomes for Bank Keshavarzi.